What is “Normal” East-West trade? - Rolf Hasse (Intereconomics, 1980)
The reduction of grain shipments and the export ban for computers imposed by the US Administration in response to the Soviet occupation of Afghanistan was supplemented, late in February 1980, by prohibition of deliveries of phosphates to the Soviet Union. President Carter has not yet urged the western industrialized states to participate in economic sanctions against the USSR, but a comprehensive embargo is still under discussion. In this connection it is not only the expediency of an embargo against the Soviet Union which is at issue, but the question how the East-West trade is to be conducted and what is, in the long run, to be regarded as normal in this field.
Keywords: 330; Embargo